Leveraging Digital Transformation to Overcome Competitive Challenges for New Entrant: A Strategic Approach For MSME Digital Bank (Study Case: Harapan Bank) - Tri Kurniawan Latif (Publikasi Indonesia, 2025)
This study explores the strategic digital transformation journey of Harapan Bank, focusing on its efforts to enhance operational efficiency, product innovation, and competitiveness in the rapidly evolving banking sector. Employing a mixed-methods approach, the research combines qualitative and quantitative methods to assess Harapan Bank's current challenges and opportunities in adopting digital banking solutions. A SWOT analysis and Technology Acceptance Model (TAM) insights reveal the bank’s strengths in customer-centric innovation and AI-driven loan profiling but highlight challenges such as operational inefficiencies, outdated infrastructure, and cultural resistance. The study identifies the vast potential in the MSME sector, particularly in rural areas, where digital banking services remain limited. The findings suggest that Harapan Bank must accelerate its digital transformation, focusing on security, product innovation, and customer-centric approaches to remain competitive against fintech rivals. The study concludes with actionable recommendations, including the adoption of MIT’s Five Building Blocks of Digital Transformation to guide Harapan Bank towards long-term success and innovation in the digital banking landscape.